Photovoltaics: New Policy Challenges for Europe - De Sousa, Luís A. (Frontiers in Energy Research, 2013)
During the past decade governments across Europe have set in place a series of programmes to expand investment on grid-connected solar power technology, most especially Photovoltaics (PV). Recently most of these programmes have been rolled back, in face of rapidly declining costs. Using a simple model this article shows that basic PV electricity costs are presently below 0.10 €/kWh in large swaths of the continent, entering levels where previously only nuclear and fossil fired electricity where found. Due to the scalable nature of PV, many households in Europe are now able to produce their own electricity at a cost considerably lower that the rates demanded by grid utilities. If governments proceed with the complete roll back of fixed electricity rates to PV suppliers the most likely result is a shift to off-the-grid systems. Long term this trend presents serious challenges to utilities and traditional electricity suppliers, putting at stake the traditional electricity market framework.